2018
DOI: 10.1016/j.envres.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted processes controlling the distribution of hazardous compounds in the spontaneous combustion of coal and the effect of these compounds on human health

Abstract: Pollution generated by hazardous elements and persistent organic compounds that affect coal fire is a major environmental concern because of its toxic nature, persistence, and potential risk to human health. The coal mining activities are growing in the state of Santa Catarina in Brazil, thus the collateral impacts on the health and economy are yet to be analyzed. In addition, the environment is also enduring the collateral damage as the waste materials directly influence the coal by-products applied in civil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In the environmental psychology literature, connectedness with nature can be seen as a psychological construct that reflects the degree to which individuals perceive that they are part of the natural environment (Schultz, 2001, 2002), and such perception arguably influences adults’ motivations to engage in pro-environmental behavior (Kals et al, 1999; Chawla, 2007; Ernst and Theimer, 2011; Cheng and Monroe, 2012; Liefländer et al, 2013; Mayer and Frantz, 2014; Richardson et al, 2016). For example, environmental activists report greater connectedness with nature compared to college students, suggesting that connectedness with nature may be related to pro-environmental attitudes and behaviors (Bruni and Schultz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the environmental psychology literature, connectedness with nature can be seen as a psychological construct that reflects the degree to which individuals perceive that they are part of the natural environment (Schultz, 2001, 2002), and such perception arguably influences adults’ motivations to engage in pro-environmental behavior (Kals et al, 1999; Chawla, 2007; Ernst and Theimer, 2011; Cheng and Monroe, 2012; Liefländer et al, 2013; Mayer and Frantz, 2014; Richardson et al, 2016). For example, environmental activists report greater connectedness with nature compared to college students, suggesting that connectedness with nature may be related to pro-environmental attitudes and behaviors (Bruni and Schultz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They believed that the HCN and NH 3 may be produced by HNCO after a series of reactions. In CFB boiler, HNCO released from pyrolysis would quickly decompose into NCO in the combustion chamber [14][15][16], while Miller [17] found that the reaction between NCO and NO reaction was the main source for N 2 O. Therefore, HNCO may be one of the main precursors of N 2 O under fluidized bed combustion.…”
Section: Ms Resultsmentioning
confidence: 99%
“…From Equations 1 and 2, we know that when the porosity is small, permeability decreases with porosity (Peña et al 2017;Oliveira et al 2018;Zhou 2017). O 2 distribution in gob is influenced by porosity.…”
Section: Movement Of Oxidized Zonementioning
confidence: 99%